Male Sexual Dysfunction and the Perpetration of Intimate Partner Violence - Hill, Terrence D. (Violence against women, 2024)
We contribute to our understanding of the social epidemiology of intimate partner violence (IPV) by developing a mediation model that frames IPV as an outcome of male sexual dysfunction (performance anxiety and erectile dysfunction) and the mechanisms of masculine discrepancy stress (the perceived failure to conform to internalized normative expectations of masculinity) and anger. Our mediation analyses of recently collected data from the 2021 Crime, Health, and Politics Survey (CHAPS), a national probability sample of 792 men, confirmed that sexual dysfunction was indirectly associated with the perpetration of any IPV, physical IPV, and sexual IPV through the compound path of masculine discrepancy stress and anger.